Follicular dendritic cell sarcoma: an unsual entity (Revista Argentina de Cirugía, 2021)
Folicular dendritic cell sarcoma is an extremelly rare lymphoid neoplasm. Lymph nodes are predominantly affected, but occasionallu extranodal compromise is seen. Definitive diagnosis requires confirmation by inmunohistochemistry. The clinical features and management are not well know. We present the case follicular dendritic cell sarcoma with axilary affectation.
Keywords: neoplasm; follicular dendritic cell sarcoma; immunohistochemistry